임상치과위생사의 유머감각과 임파워먼트와의 관계 - 김영임; Young Im Kim (Han'guk Ch'iwisaeng Hakhoe chi, 2014)
Objectives : The purpose of the study is to investigate the relationship between humor andempowerment in clinical dental hygienist. Methods : Subjects were 374 clinical dental hygienist in Jeollabuk-do from April 20 to June4, 2013. Data were analyzed using the statistical package SPSS WIN 12.0 for frequency, meanand standard deviation analysis, one-way ANOVA and linear regression. Results : The mean score or the clinical dental hygienist of humor was 2.55 out of 4 eachof the sub-dimensions including emotional expressiveness, message sensitivity and preference ofhumor. Empowerment was 3.50 out of 5 and each of the sub-dimensions including meaning,competence, self-determination and impact. There was a significantly positive correlation betweenthe sense of humor and the empowerment. Conclusions : It is necessary to develop the empowerment combined with humor sense inthe curricula of dental hygiene education and leadership management in the clinical dental hygienist.